Activated platelets kill Staphylococcus aureus, but not Streptococcus pneumoniae—The role of FcγRIIa and platelet factor 4/heparinantibodies. (24th April 2020) - Wolff, Martina; Handtke, Stefan; Palankar, Raghavendra; Wesche, Jan; Kohler, Thomas P.; Kohler, Christian; Gruel, Yves; Hammerschmidt, Sven; Greinacher, Andreas
Abstract: Background: Heparin induced thrombocytopenia (HIT) is likely a misdirected bacterial host defense mechanism. Platelet factor 4 (PF4) binds to polyanions on bacterial surfaces exposing neo‐epitopes to which HIT antibodies bind. Platelets are activated by the resulting immune complexes via FcγRIIA, release bactericidal substances, and kill Gram‐negative Escherichia coli . Objectives: To assess the role of PF4, anti‐PF4/H antibodies and FcγRIIa in killing of Gram‐positive bacteria by platelets. Methods: Binding of PF4 to protein‐A deficient Staphylococcus aureus (SA113Δ spa ) and non‐encapsulated Streptococcus pneumoniae (D39Δ cps ) and its conformational change were assessed by flow cytometry using monoclonal (KKO, 5B9) and patient derived anti‐PF4/H antibodies. Killing of bacteria was quantified by counting colony forming units (cfu) after incubation with platelets or platelet releasate. Using flow cytometry, platelet activation (CD62P‐expression, PAC‐1 binding) and phosphatidylserine (PS)‐exposure were analyzed. Results: Monoclonal and patient‐derived anti‐PF4/H antibodies bound in the presence of PF4 to both S. aureus and S. pneumoniae (1.6‐fold increased fluorescence signal for human anti‐PF4/H antibodies to 24.0‐fold increase for KKO). Staphylococcus aureus (5.5 × 10 4 cfu/mL) was efficiently killed by platelets (2.7 × 10 4 cfu/mL) or their releasate (2.9 × 10 4 cfu/mL). Killing was not further enhanced by PF4 or anti‐PF4/H antibodies. Blocking FcγRIIa had no impact on killing of S. aureus by platelets. In contrast, S. pneumoniae was not killed by platelets or releasate. Instead, after incubation with pneumococci platelets were unresponsive to TRAP‐6 stimulation and exposed high levels of PS. Conclusions: Anti‐PF4/H antibodies seem to have only a minor role for direct killing of Gram‐positive bacteria by platelets. Staphylococcus aureus is killed by platelets or platelet releasate. In contrast, S. pneumoniae affects platelet viability.